Combining System Models and CAD for Change Scenario Management - Hick, Hannes; Schleich, Benjamin; Sanladerer, Stefan; Ryan, Karen; Trautner, Jessica; Piguet, Jean; Wilking, Fabian; Horber, Dennis; Faustmann, Clemens; Kranabitl, Philipp; Kollegger, Stefan; Bajzek, Matthias; et al. (33rd Annual INCOSE International Symposium, 2023)
In the development of complex mechatronic systems, interdisciplinary cooperation requires an exchange between stakeholders in order to ensure fulfillment of requirements and related functions. The cooperation of the stakeholders from different disciplines must be well coordinated to address systems changes. The system model as an essential aspect of model-based systems engineering, has to be linked to specific models of involved disciplines (mechanical, electrical/electronical and software) to enable a basis for automatic identification e.g., of affected subsystems and functions. This contribution discusses the potential of model linking from the perspective of change scenarios by considering published approaches to link system models and computer-aided design (CAD). A methodical approach on how descriptive system models can be used as base for computer-aided design is presented. This approach is analyzed by reviewing a use case for a design change scenario of an automotive eAxl
Keywords: MBSE